Importance of oxygen atmosphere to recover the ZnO-based varistors properties - Ramirez, M. A.; Simoes, A. Z.; Bueno, Paulo Roberto [UNESP]; Marquez, M. A.; Orlandi, Marcelo Ornaghi [UNESP]; Varela, José Arana [UNESP] (Springer, 2006)
A methodology to recover the non-ohmic properties of ZnO based varistors after degradation with long and short duration pulses was proposed in this work. The basic idea consists in submitt the degraded ceramics at different temperatures and oxygen flows. Thermal treatment at 900 degrees C for 2 h with oxygen flow of 15 l/h allowed to obtain better non-linear coefficient (alpha= 52.5) compared to the standard sample. Rietveld refinement showed that with the thermal treatment, the oxygen species and the beta-Bi2O3 phase, lost in the degradation process, are recovered in the grain boundary.